SOSIALISASI PENGENALAN SANGGAR MERAH MERDEKA SEBAGAI ORGANISASI PEDULI ANAK SURABAYA MELALUI JINGLE - Hilda Yunita Wono; Fika Fatimah; Agung Prasetyo; Yavrina Syafarani (PeKA: Jurnal Pengabdian Kepada Masyarakat, 2022)
Throughout the pandemic, all levels of society still want to continue to carry out their normal lives and activities. Including in carrying out life as individuals and in society. An example of this is community service activities that have a positive impact on the dynamics of community life. Community service is also an activity that fosters self-awareness of one’s surroundings. This self-awareness allows people to pay more attention, as a symbol of humanity. Humanity itself is an essential nature of humans that distinguishes them from other creatures. As a human being, it is something that must be done to have a greater sense of humanity towards others. The method that can be done to create a greater sense of humanity is community service. Community service can be done by anyone, including students who are studying. This activity will provide great learning in terms of socialization and living as a community side by side. Community service can be done. One of which is by socializing the positive activities that are carried out by suburban child service organizations in Surabaya. This will have an impact on the community who lacks awareness to know and participate in community service. One of them is by participating in campaigning and promoting childcare organizations to the community. One small thing that is implemented for a good purpose will shape the character and character, especially of the younger generation of Indonesia to be improved. Improving the nature and character will create leaders who have a high social spirit and that is what is needed by the Indonesian state.